Rehabilitation of Power Quality in Electric Distribution System by implementing High Voltage Distribution System (HVDS) & Dispersed Generation (DG) - S. S. Sarma, B. Ashok Kumar, Dr. S. Jayalakshmi, Dr. J. Ranga, Dr. M. Murali (International Journal of Control and Automation, 2020)
This paper presents the comparison of existing low voltage distribution system with proposed high voltage distribution system. The Main objective of this paper is to present the reduction of active power losses and maintain voltage profile constant in Electric Distribution system by implementing High Voltage Distribution System (HVDS) over Low Voltage Distribution System (LVDS). In India, the average transmission and distribution losses have been officially indicated as 28% of the electricity generated, because of the fact of usage of existing distribution system. As for the low voltage in existing distribution system, current is high which leads to high power losses and also allow the hooking and hence power theft. Since loss reduction in distribution system is of keen importance and main reason behind these losses is the use of low voltage for distribution in existing system. Hence to overcome all these problems, implementation of high voltage distribution system and installing Dispersed Generation (DG) units is considered as the best move to enhance the performance of distribution system. In this paper, MATLAB simulation is applied to Distribution System before implementing HVDS and after implementing the HVDS. The Voltage profiles and Power Losses are observed in both the cases with and without using DG units. In overall economic point of view, annual savings and payback period is also determined.